Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1001/archinte.165.13.1458
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Therapy Practices in US Hospitals in an Era of Practice Guidelines

Abstract: A significant percentage of hospitalized patients do not receive adequate antithrombotic therapy for the primary and secondary prevention of thromboembolic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 43 publications
3
99
3
3
Order By: Relevance
“…19,20 The results of a large postal survey of orthopaedic surgeons showed only 42% prescribe an extended duration of VTE prophylaxis beyond discharge, nearly all of which use aspirin. 21 However, the use of aspirin for extended VTE prophylaxis is now questioned since the Pulmonary Embolism Prevention (PEP) study of over 4000 total hip and knee replacements concluded that aspirin provides no benefit over placebo, whilst the 160 mg dosage has an associated significant risk of gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The results of a large postal survey of orthopaedic surgeons showed only 42% prescribe an extended duration of VTE prophylaxis beyond discharge, nearly all of which use aspirin. 21 However, the use of aspirin for extended VTE prophylaxis is now questioned since the Pulmonary Embolism Prevention (PEP) study of over 4000 total hip and knee replacements concluded that aspirin provides no benefit over placebo, whilst the 160 mg dosage has an associated significant risk of gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature has largely focused on the need of thromboembolic prophylaxis, providing efficacy evidence, when performed in the manner and appropriate times [10,11].…”
Section: Medical Liability In Prevention Diagnosis and Treatment Ofmentioning
confidence: 99%
“…34 It has an immediate onset of action after intravenous administration and a short half-life (25 minutes in patients with normal renal function). 35 Bivalirudin alone and in combination with a GP IIb/IIIa inhibitor were compared with heparin (UFH or enoxaparin) plus a GP IIb/IIIa inhibitor in the ACUITY study, a randomized, controlled, noninferiority study of more than 13,000 patients with NSTEMI scheduled to undergo angiography. 36 Most patients received clopidogrel.…”
Section: Anticoagulant Therapiesmentioning
confidence: 99%
“…35 Overlap of parenteral and oral anticoagulant therapies was appropriate in 246 (51%) of the 486 patients who received overlapping therapies. Most patients were not discharged from the hospital until after parenteral therapy was discontinued.…”
Section: ■■ Vte Treatmentmentioning
confidence: 99%
See 1 more Smart Citation